2018
DOI: 10.1002/pbc.27011
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Ewing sarcoma: Is detection by imaging follow‐up protocol associated with survival advantage?

Abstract: FUIP may benefit survival in EwS relapse, especially in lung recurrence. Pain was the leading symptom of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…[21][22][23] The current study is limited by its retrospective design. [21][22][23] The current study is limited by its retrospective design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] The current study is limited by its retrospective design. [21][22][23] The current study is limited by its retrospective design.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies assessing the value of routine imaging in other soft-tissue and bone sarcomas have shown contradictory results, and this illustrates the necessity for tumorspecific studies assessing the value of surveillance imaging because its value is dependent on tumor-specific factors (eg, tumor biology and chance of survival after relapse). [21][22][23] The current study is limited by its retrospective design. We tried to limit this bias by using a standardized case report form.…”
Section: Discussionmentioning
confidence: 99%
“…6,114 At the time of relapse, about 52% of patients have symptoms, while remaining patients are diagnosed during follow-up imaging. 117 The most important prognostic factors are interval between initial diagnosis and subsequent relapse, and site of relapse. Other prognostic factors for poor survival at relapse include high LDH at relapse, age >15 years, nonpulmonary metastasis and symptomatic relapse.…”
Section: Ewing Sarcoma [Ews]/primitive Neuroectodermal Tumor [Pnet]mentioning
confidence: 99%
“…Different opinions about whether surgical margin and recurrence affect metastasis and survival [22,23]. Some studies suggested safe surgical margin only affects recurrence, and recurrence didn't increase metastasis and reduce survival [24][25][26]. However, more studies suggested the risk of local recurrence was leading to metastasis and reducing survival [6,27,28].…”
Section: Discussionmentioning
confidence: 99%